2012
DOI: 10.1080/01932691.2011.574924
|View full text |Cite
|
Sign up to set email alerts
|

Water-Diesel Microemulsions Stabilized by an Anionic Extended Surfactant and a Cationic Hydrotrope

Abstract: Alcohol-free microemulsions were formulated using mixtures of extended surfactant (C 12-14 -PO 14 -EO 2 SO 4 Na), sodium dodecyl benzene sulfonic acid and cationic hydrotropes with equal amounts of water and diesel. The cationic hydrotropes had short hydrocarbon or propylene oxide chain. The formulation included sodium carbonate to convert naphthenic acids in diesel to soaps. The phase behavior at ambient temperature of oil-free mixtures as a function of NaCl concentration was investigated. Visual inspection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Thus, another advantage of using mixed anionic and cationic surfactants is that the surfactant mixture can mitigate the need for salt addition to achieve a middlephase microemulsion (e.g., addition of a cationic surfactant to an anionic surfactant solution can replace the need for salt addition). Kayali et al (2012) observed that minimum surfactant and salt were required to obtain alcohol-free middle-phase microemulsion of diesel when a cationic surfactant was added, which was in agreement with Li et al (2017) who obtained middle-phase microemulsions with crude oil in the addition of modest amounts of cationic surfactants to anionic surfactants.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Thus, another advantage of using mixed anionic and cationic surfactants is that the surfactant mixture can mitigate the need for salt addition to achieve a middlephase microemulsion (e.g., addition of a cationic surfactant to an anionic surfactant solution can replace the need for salt addition). Kayali et al (2012) observed that minimum surfactant and salt were required to obtain alcohol-free middle-phase microemulsion of diesel when a cationic surfactant was added, which was in agreement with Li et al (2017) who obtained middle-phase microemulsions with crude oil in the addition of modest amounts of cationic surfactants to anionic surfactants.…”
Section: Introductionsupporting
confidence: 84%
“…Mixtures of anionic and cationic surfactants have the potential to exhibit significant synergistic effects ( e.g ., low critical micelle concentration [CMC], ultralow interfacial tension [IFT], middle‐phase microemulsion formation, high adsorption, and elevated solubilization) (Alexandrova et al, 2020; Antón et al, 1993; Antón et al, 2008; Jadidi et al, 2013; Kame et al, 1973; Kanasaki et al, 2016; Kayali et al, 2010a; 2010b; Li et al, 2017; Lioi et al, 2009; Liu and Rosen, 1996; Sohrabi et al, 2008; Stocco et al, 2010; Tah et al, 2011; Wang et al, 2016). This potential synergism can greatly enhance the performance of surfactant‐related applications ( e.g ., detergency, anticorrosion, surfactant‐enhanced aquifer remediation, and enhanced oil recovery, and alternative fuel applications) (Jadidi et al, 2013; Javadian et al, 2013; Karapanagioti et al, 2005; Kayali et al, 2012; Li et al, 2017; Schulz et al, 2016; Wellington and Richardson, 1997). However, anionic–cationic surfactant mixtures (structure and compositions) and external variables are known for producing other phases ( e.g .…”
Section: Introductionmentioning
confidence: 99%
“…Fossil fuels are the main source of energy in the modern world. Diesel is used in transportation, the production of electricity, and industrial activities; however, it is associated with the emission of particulate matter, black carbon, sulfur oxides, nitrogen oxides (NO x ), carbon monoxide, and carbon dioxide (CO 2 ) [105,106]. Thus, a technology capable of reducing these pollutants without compromising engine performance is needed.…”
Section: Application In Formulation Of Fuelsmentioning
confidence: 99%
“…Besides, 1-butanol, which is miscible with diesel fuel oil, can also be used in the blending of diesel fuel with aqueous ethanol. Strey et al [10,11] have reported some essential studies of water-diesel microemulsions.…”
Section: Introductionmentioning
confidence: 99%